Comparative assessment of antioxidant properties of polyphenols from heartwood and Maackia amurensis callus culture - O. V. Azarova; V. M. Bryukhanov; V. P. Bulgakov; Ya. F. Zverev; V. V. Lampatov; S. A. Fedoreyev (Бюллетень сибирской медицины)
On long-term introduction to rats in dosage 100 mg/kg polyphenol complexes from heartwood and callus culture of Maackia amurensis Rupr. et Maxim. had a marked influence on the activity of free radical oxidation. Under conditions of induced oxidant stress both polyphenol complexes inhibited prooxidant activity directly affecting the products of free radical oxidation. Inhibiting influence on the production of oxygen active forms that is characteristic for both phytocomplexes is determined by inhibition of mechanisms both enzymatic and non-enzymatic defense.